Love in Nursing: A Concept Analysis - Mohsen Adib Hajbaghery; Shahnaz Bolandian (Journal of Caring Sciences, 2020)
Intruduction: Professional nursing is based on caring. Care is a combination of love and respect in interacting with others. There are many concerns about nursing care without love. However, the concept and meaning of love in nursing have not been paid the due attention. This study analyzed the concept of love in nursing. The aim of this study is to describe and discuss the concept of love in nursing. Methods: A concept analysis was conducted using the 8-step Walker and Avant's model. Databases such as SID, PubMed, Web of Science, CINHAL, SCOPUS and Google Scholar were searched. The terms "love","concept analysis" and "nursing" were used for searching in international sources. No time limit was considered in searching the databases and all studies were published until December 2017. In the initial search, 142 articles were found but finally eight articles remained relevant and entered the study. Results: The authors did not find a special independent tool to measure love in nursing. Therefore, we define love in nursing as follows: the combination of nursing care with a sense of responsibility, benevolence, attention and concern, respect, and understanding of others as a human being, regardless of their negative consequences for themselves. Conclusion: Understanding the meaning of love in nursing can promote nursing practice in two ways. First, the nurses are examining their values and beliefs. Second, they find out how to interact with patients.